A controvérsia da quantificação do dano moral: uma análise jurisprudencial dos casos de negativação indevida perante os tribunais de justiça do país - Santos, Ananda Ferreira dos (2018)
The purpose of the present work is to address the path taken by magistrates in the quantification of moral damages, given the complexity of the subjective nature of this type of damage and the absence of fixed parameters that provide guidance during the assessment of the due compensation. To that end, 27 judges of the country's courts were examined on undue denial in the register of bad debtors, in order to analyze how the assessment of compensation for moral damages in the day-to-day affairs of the Courts behaves, especially in similar cases . In addition, it was previously carried out an explanatory approach on Civil Liability and its elements, also passing through some criteria outlined in the legal literature, which are used as support for the foundation of the judgments and the effective fixation of the quantum debeatur. Thus, the jurisprudential study made it possible to see which criteria were included in the grounds of the judgments, so that it also facilitated a critical and expositive analysis of how the motivation for decisions develops, which is superficial and insufficient, also showing some incongruities detected in the analyzed cases